RESEARCH OF THE FEATURES OF TOURISM DEVELOPMENT AND ITS TERMINOLOGY - Rustamova, Shahnoza; Turg`unova Fazilat Rustam qizi (Журнал иностранных языков и лингвистики, 2023)
Our article will be devoted to the development of tourism, the conceptual system of tourism in the studied languages ​​, and its structural features will be studied. Determines the characteristics of the lexicographical description of tourism terminology in multilingual publications.